"Iron catalyzed alkynylation of thiohydantoins with terminal alkyne via cross-dehydrogenative coupling (CDC)". (3rd August 2021) - Morja, Mayur I.; Chauhan, Prakashsingh M.; Chikhalia, Kishor H.
Graphical abstract: Abstract: Herein, A novel strategy for Iron(II)-catalyzed alkynylation of thiohydantoins with terminal alkyne has been firstly reported. Optimization study was carried out through various catalysts, oxidants and solvents. The merit of this strategy is illustrated by the breadth of functional groups tolerated in the transformation. This study offers a unified method to access several alkynylated thiohydantoins in moderate to higher yield via C(sp 3 )-C(sp) bond formation.